Peak overpressure and impulse due to diffraction over a cylinder and/or multi-reflection of a shock wave in structural design- Part I. Issue 1 (March 2021) - Hahn, Andreas; Mensinger, Martin; Rutner, Marcus
The design and planning of structural components, such as columns, to resist blast loads is a complex task. Often standard free-field blast loads, specified in design codes or other literature, are used for the analysis of the object. These loads are then further increased or decreased depending on the topology of the surrounding geometry (Mach-Stem), the shape of the impacted object itself, and blast wave reflection. However, most of these research works focus purely on the assessment of the structural components itself, ignoring a complex fluid mechanics phenomenon such as diffraction, which is of particular interest when circular columns are standing next to each other or placed in front of a façade. The article addresses three main topics. First, the article answers the question whether the area behind the column is protected, meaning constituting a shadowed area. We present findings that the close area behind a column is subjected to higher pressure and impulse values as there would be without the column. Hence, the incident pressure sees significant pressure buildup due to diffraction. This pressure buildup is quantified using pressure increase factors and presented together with the accompanying impulse. Second, this pressure buildup is of relevance for realistic design of a façade behind the column, which is not covered in current design codes at all. We discuss relevant parameters in the design process. Third, directly coupled with the assessment of the pressure buildup behind the column due to diffraction is the assessment of pressure and impulse in the area behind the column due to multi-wave reflection at a façade, leading to a significant pressure and impulse scale-up, which might be relevant for design of a column and/or a façade. This article identifies gaps in understanding diffraction and subsequent multi-reflection of blast wave within a structural design framework and provides insights on how to establish safe design accounting for these effects.